RELATIONSHIP BETWEEN RAGA RAGINI AND ENVIRONMENT: राग रागिनी और पर्यावरण का परस्पर सम्बन्ध - Agrawal, Varsha (International Journal of Research -GRANTHAALAYAH, 2015)
The mind and the mind attached to it are enamored by looking at our geographical environment and the body with a good clean environment leads the human mind towards peace. The focus of various raga-raganis in Indian music is a close relationship with the environment. It is well known that a good thinking, good thoughts, good music etc. all create a good environment. The flow of the river, the flow of air, the noise of trees all create a pleasant musical sound that is supernatural, universal. But in our Samaveda, the pronunciation of Oun, the chanting of mantras, the effect of its sound along with the eloquence, the resonance, the tone of the atmosphere, on the human mind and brain refreshes the mental environment along with the geographical environment and imparts consciousness and consciousness. Therefore, if along with biology, botanical and scientific efforts, all the raga-raginis of Indian music will be used for conservation of the environment, then it will be a perfect and complete tool. In this present age, environmental protection is an important issue and debate on it is to find its remedies and to present them on the path of world welfare. मन और उससे जुड़ा मस्तिष्क जिस प्रकार हमारे भौगोलिक पर्यावरण को देखकर उस पर आसक्त होता है और शरीर को अच्छे स्वच्छ पर्यावरण का साथ मानव मन को सुख शान्ति की ओर ले जाता है। भारतीय संगीत में विभिन्न राग-रागनियों का ध्यान पर्यावरण के साथ घनिष्ठ सम्बन्ध है। ऐसा सर्वविदित है कि एक अच्छा सोच, अच्छे विचार, अच्छा संगीत आदि सभी अच्छे पर्यावरण का निर्माण करते हैं। नदी का बहना, वायु का प्रवाहमान होना, वृक्षों की सांय-सांय सभी एक सुखद संगीत ध्वनि का निर्माण करते हैं जो अलौकिक है, सार्वभौमिक है। परन्तु हमारे सामवेद में ऊँ का उच्चारण, मंत्रों का उच्चारण उद्दात, अनुद्दात, स्वरित के साथ उसकी ध्वनि का वायुमण्डल पर असर मानव मन और मस्तिष्क पर भौगोलिक पर्यावरण के साथ मानसिक पर्यावरण को तरोताजा कर स्फूर्ति और चेतना प्रदान करता है। अतः पर्यावरण के संरक्षण हेतु यदि जैविकी, वानस्पतिकीय व वैज्ञानिक प्रयासों के साथ-साथ भारतीय संगीत की समस्त राग-रागिनियों का भी प्रयोग किया जाएगा तो वह उत्तम और सम्पूर्ण साधन होगा। आज के इस वर्तमान युग में पर्यावरण सरंक्षण महत्वर्पूण मुद्दा है व इस पर बहस होना इसके उपायों को खोजना और उनको प्रतिपादित करना विष्व के कल्याण के पथ पर अग्रसर होना है।